ISLAM INKLUSIF DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM SLTA - M Ajib Hermawan (IAIN Purwokerto, 2015)
Abstract: The results of this study indicate that the curriculum of Islamic education that is applied in the high school has actually accommodate and integrate an inclusive paradigm of Islam, though in some aspects there are still parts that show the truth of Islam dogmatism which tend to be proprietary. Moreover, the existence of inclusive Islamic discourse contained in PAl in high school curriculum can be seen through some of the themes material on subjects PAI discussion. By following the path-based studies it is seen that an academic subject matter aqidah as a basis for the development has space for integrating Islam inclusive leaming by relating PAI material of al-Qur'an. More concrete fom is the material in which the discussion about the morality of commendable and despicable behavior has the possibility to introduce inclusive Islamic discourse. Meanwhile, for the matter of jurisprudence and history is generaly limited by the discussion tend to be proprietary. Keywords: Inclusive Islam, PAI high school curriculum.